2014
DOI: 10.1115/1.4027871
|View full text |Cite
|
Sign up to set email alerts
|

Random Matrix Approach: Toward Probabilistic Formulation of the Manipulator Jacobian

Abstract: In this paper, we formulate the manipulator Jacobian matrix in a probabilistic framework based on the random matrix theory (RMT). Due to the limited available information on the system fluctuations, the parametric approaches often prove to be inadequate to appro-priately characterize the uncertainty. To overcome this difficulty, we develop two RMT-based probabilistic models for the Jacobian matrix to provide systematic frameworks that facilitate the uncertainty quantification in a variety of complex robotic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Here, we present the RMT-based formulation of the manipulator Jacobian matrix developed in our earlier studies [10], [12]. In a system with motion uncertainty, the inverse differential kinematic equation can be considered as a general stochastic differential equation given by dq dt = f (q, ω, t)…”
Section: A Motion Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present the RMT-based formulation of the manipulator Jacobian matrix developed in our earlier studies [10], [12]. In a system with motion uncertainty, the inverse differential kinematic equation can be considered as a general stochastic differential equation given by dq dt = f (q, ω, t)…”
Section: A Motion Uncertainty Analysismentioning
confidence: 99%
“…Let us now assume that the upper bound on the Frobenius norm of the J k is known and denoted as u, i.e., J F ≤ u. We showed that [12] this constraint along with the model described by Eq. ( 16) leads to the inequality tr nΣ ≤ u 2 − J k 2 F .…”
Section: A Motion Uncertainty Analysismentioning
confidence: 99%
“…The robustness of the second-order approximation as well as its superiority compared to the first-order method was verified in different numerical examples. Sovizi et al [14][15][16][17][18] proposed an uncertainty characterization method in complex robotic manipulators based on the random matrix theory (RMT). It was shown that RMT-based models can appropriately capture the uncertainty only using limited information about the system variation.…”
Section: Introductionmentioning
confidence: 99%